Understandable electric circuits - Wang, Meizhong 1955- (Raleigh, NC SciTech Publishing, 2010)
This unique and well-structured book provides understandable and effective introduction to the fundamentals of DC/AC circuits including: current; voltage; power; resistor capacitor; inductor; impedance; admittance; dependent/independent sources; basic circuit laws/rules (Ohm's law, KVL/KCL, voltage/current divider rules); series/ parallel and wye/delta circuits; methods of DC/AC analysis (branch current and mesh/node analysis); the network theorems (superposition, Thevenin's/Norton's theorems, maximum power transfer, Millman's and substitution theorems); transient analysis; RLC circuits and resonance; mutual inductance and transformers and more.
Electronic reproduction.
Keywords: Electric circuits; Capacitors; Electric inductors; Electric resistors; Electric transformers; Impedance (Electricity).; Transients (Electricity).; Voltage dividers; Electronic books